Sosialisasi Gizi dan Penyuluhan Keluarga Berencana Sebagai Upaya Menurunkan Angka Stunting di Desa Kemiri - Budi Prabowo; Annisa Lailatul Qomariyah; Fitra D. P. I. Santoso; Palupi, Kirana Woro; Luana Shiany Margareta; Salsabila Mona Odelia (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Stunting is a chronic nutritional problem in young children that has serious implications for physical growth, cognitive development, and individual productivity. This condition is caused by a range of complex factors, including poor maternal nutrition and environmental conditions affecting quality of nutrition. The first 1,000 days of life represent a critical period for stunting prevention, as children's brain growth and development are particularly rapid during this time. Socialization regarding the importance of balanced nutrition and Family Planning programs is a strategic step to support optimal child growth and prevent stunting. This program begins with obtaining permits and coordinating with the Head of Kemiri Village to identify appropriate targets, as well as involving local neighborhood association in surveying facilities and infrastructure. The initiative aims to raise awareness in Kemiri Village about stunting and its prevention, and to educate the importance of balanced nutrition for supporting optimal child growth. Through socialization and counseling, it is hoped that the community will be able to recognize signs of stunting and take appropriate actions. This aligns with the village’s sustainable development goals (SDGs), particularly in achieving the target of a hunger-free village. By reducing the prevalence of stunting, the quality of life for the community can be significantly improved.